Catalyzing plant science research with RNA-seq - Martin, Laetitia; Fei, Zhangjun; Giovannoni, James; Rose, Jocelyn K. (Frontiers in Plant Science, 2013)
Next generation DNA sequencing technologies are driving increasingly rapid, affordable and high resolution analyses of plant transcriptomes through sequencing of their associated cDNA (complementary DNA) populations; an analytical platform commonly referred to as RNA-sequencing (RNA-seq). Since entering the arena of whole genome profiling technologies only a few years ago, RNA-seq has proven itself to be a powerful tool with a remarkably diverse range of applications, from detailed studies of biological processes at the cell type-specific level, to providing insights into fundamental questions in plant biology on an evolutionary time scale. Applications include generating genomic data for heretofore unsequenced species, thus expanding the boundaries of what had been considered “model organisms,” elucidating structural and regulatory gene networks, revealing how plants respond to developmental cues and their environment, allowing a better understanding of the relationships between genes and their products, and uniting the “omics” fields of transcriptomics, proteomics, and metabolomics into a now common systems biology paradigm. We provide an overview of the breadth of such studies and summarize the range of RNA-seq protocols that have been developed to address questions spanning cell type-specific-based transcriptomics, transcript secondary structure and gene mapping.